TAHAP-TAHAP SOSIALISASI TERAPIS DALAM PENANGANAN ANAK AUTIS DI YAYASAN PERMATA HATI PEKANBARU - Zico Pratama; Tengku Romi Marnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aim to describe and analyse critically about the stages of socialization therapist in dealing with children autism in the Permata Hati Pekanbaru Foundation, and the involvement of parents in the treatment of children with autism. The results of this study, expected to be used as a motivation for caregivers to be able to constantly improve its business in developing children surrogate so that they can be independent.This research is a field research using qualitative descriptive analysis by taking a subject teacher (therapist) in Permata Hati Pekanbaru Foundation and parents of students with autism. The object of this research is about the stages of socialization in the treatment of children with autism are applied by a therapist at Permata Hati Pekanbaru Foundation. Data were collected by interview, observation and documentation.The results of this study indicate that teachers or therapists and families play an important role in socializing in dealing with children with autism early. Stages of socialization by the therapist in dealing with children with autism is the stage of diagnosis, observation, and Follow-up phase. Social interaction and communication skills in children at school can, proved therapist is able to produce surrogate children have to interact and communicate progress although it still requires scrutiny of others. To support the increased socialization of children with autism, parents become agents of socialization is very important as well. The involvement of parents in providing counseling services are needed in the development of children. So the need for good cooperation between teachers and parents in dealing with children with autism.Keywords: Autism, The Stages of socialization, Parents